Self-lubricating glass composite magnesium carbide nanocoating - Shchepetov, V.V.; Fialko, N.M.; Bys, S.S. (Problems of Tribology, 2025)
The results of the study of the friction and wear characteristics of the developed nanostructured glass composite self-lubricating coatings are presented, the structural components which through magnesium carbide have a qualitative effect on the graphitization process due to the formation of a surface layer of carbide α-graphite, which, when combined with surface oxides characterized by low shear resistance, performs the role of solid lubricants under friction conditions. The positive role of the glass phase in the form of aluminoborosilicate, which affects the tribotechnical properties of coatings, has been established. It has been determined that the increase in adhesion strength is achieved by forming a surface layer of vitreous sodium silicate during spraying. It has been found that the intercalation of the graphite layer with dispersed particles of the surface structure does not significantly affect the tribotechnical characteristics. The developed nanostructured glass composite coatings showed high antifriction characteristics